The Role of Human Gut Microbe Ruminococcus gnavus in Inflammatory Diseases - Sasmitra Kandasamy; Vengadesh Letchumanan; Kar Wai Hong; Kah-Ooi Chua; Nurul Syakima Ab Mutalib; Alvin Lai Oon Ng; Long Chiau Ming; Hui Xuan Lim; Sivakumar Thurairajasingam; Jodi Woan-Fei Law; Loh Teng-Hern Tan (Progress in Microbes and Molecular Biology)
Dysbiosis is a prominent factor in numerous inflammatory conditions, with Ruminococcus gnavus, a prevalent gut microbe, implicated in inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), eczema, metabolic disorders, and rheumatic diseases. R. gnavus contributes to inflammation by producing an inflammatory polysaccharide and degrading mucin. The increasing evidence of elevated R. gnavus abundance in various inflammatory conditions suggests its potential as a therapeutic target. Despite this, there are limited studies on treatment strategies targeting R. gnavus. This article provides a comprehensive overview of the association between R. gnavus and diverse inflammatory conditions, highlighting the need for further research to explore effective treatment options against this bacterium.